2007
DOI: 10.1210/en.2007-0754
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Central Leptin and Resistin on Body Weight, Insulin Resistance, and β-Cell Function and Mass by the Modulation of Hypothalamic Leptin and Insulin Signaling

Abstract: To determine the long-term effect of central leptin and resistin on energy homeostasis, peripheral insulin resistance, and beta-cell function and mass, intracerebroventricular (ICV) infusion of leptin (3 ng/h), resistin (80 ng/h), leptin plus resistin, and cerebrospinal fluid (control) was conducted by means of an osmotic pump for 4 wk on normal rats and 90% pancreatectomized diabetic rats fed 40% fat-energy diets. Overall, the effects were greater in diabetic rats than normal rats. Leptin infusion, causing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 39 publications
8
65
0
4
Order By: Relevance
“…Resistin has been reported to stimulate proliferation of different cellular types (Calabro et al 2004, Ort et al 2005, Mu et al 2006, Park et al 2008. Conversely, resistin-13 peptide, a fragment of human resistin possessing some biological activity of the entire hormone, inhibited the proliferation of the breast cancer …”
Section: Discussionmentioning
confidence: 99%
“…Resistin has been reported to stimulate proliferation of different cellular types (Calabro et al 2004, Ort et al 2005, Mu et al 2006, Park et al 2008. Conversely, resistin-13 peptide, a fragment of human resistin possessing some biological activity of the entire hormone, inhibited the proliferation of the breast cancer …”
Section: Discussionmentioning
confidence: 99%
“…Chronic studies, on the other hand, show increased muscle glucose uptake in chow fed rats [150,152]. Conversely, although leptin is able to influence hepatic glucose flux in DIO rats [154], chronic ICV leptin in DIO rats is unable to restore insulin-induced increases in glucose uptake [153]. However, these seemingly discordant results may be secondary to different diets, leptin doses, and/or the sex of the rats.…”
Section: Cns Control Of Skeletal Muscle Uptakementioning
confidence: 99%
“…Given that leptin serves as long-term adiposity signal, it follows that chronic ICV administration of leptin would have more potent effects on glucose homeostasis. Considering that high fat diets and obesity have been shown to cause CNS leptin resistance in regards to anorexia, it is surprising that in several different models, including DIO rats, short term overfed rats, and insulinopenic rats, chronic ICV leptin consistently decreases HGP [150,[152][153][154]. These effects may have something to do with the specific signaling pathways activated by leptin.…”
Section: Cns Control Of Hepatic Glucose Productionmentioning
confidence: 99%
“…It was also observed that glutamate was synthesized from butyrate 13 C atoms, indicating that acetyl-CoA from butyrate degradation is also entering Kreb's cycle. RETN is a hormone that represses the uptake of glucose by cells and has been implicated in insulin resistance (23), and its overexpression (as shown here) indicates that butyrate-preselected HCT15 cells prefer to metabolize butyrate rather than glucose. RETN has also been described in throphoblastic cells as being responsible for GLUT1 down-regulation (24) as we saw in HCT15 butyrate-preselected cells.…”
Section: Discussionmentioning
confidence: 57%